The Dramaturgy of Politics and Power in Determining Budget Problem in District Jembrana, Bali. (25th November 2015) - Syarifuddin,
Abstract: The purpose of this study is to analyze budget policies that made basic education services in Jembrana free. This study analyzed the perceptions and interpretations of public and government toward education. Analysis is performed by using Erving Goffman dramaturgy method which shows the front stage and back stage where the actors interact. The study found that in order to create power for budget perpetrators, the patterns of organization openness needs to be created. Which means that by raising the issue of basic needs, the actor will then receive comprehensive support.